(untitled) (Zoo Botanica, 2025)
The global population is increasing, while the amount of arable land is decreasing due to desertification and salinization, both of which are primarily caused by human activities, such as climate change. Global climate scenarios and food security will be fundamentally altered by increased temperatures; the entire ecosystem will be altered. This review examines the remarkable resilience of Chenopodium quinoa Willd. can provide or support ecosystem services in a sustainable approach to ameliorating impacts such as famine. In contrast to the conventional food staples, quinoa exhibits remarkable resilience to abiotic stresses and is a highly nutritious crop with a distinct nutritional profile. As such, it holds potential importance for ensuring food security and nutritional adequacy. With regard to the growing worldwide population, the consequences of climate change, desalination, phytoremediation, nutrient deficit, and poverty alleviation, this crop has the ability to improve global conditions